(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In article the problem of methodology of anthropology, a discourse orientation about the person, self-understanding of the person, a perspective of the transcendental are raised. The discourse is realized as a special phenomenon, as difﬁ cult, system education as multidimensional and multilevel essence, discourses of social institutes, or institutional discourses (scientiﬁ c, pedagogical, religious, art and esthetic, legal, political, mass media, etc.), texts are objectiﬁ ed in jointly generated and broadcasted by them (the ordered sign sets) a certain type of consciousness (scientiﬁ c, pedagogical, mystical, art, legal, political, public, mass), designated or generalized in the social purpose of institute and, respectively, in a root basic, base, key concept of a discourse are formed. Keywords: discourse, transcendental, subjectivity, death of the person, postmodernism, post-structuralism.